Applications and Design for a Cloud of Virtual Sensors - Ammar Jameel Hussein; Ammar Riadh; Mohammed Alsultan; Abd Al-razak Tareq (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The use of sensors in our daily lives is a growing demand with the large number of electronic devices around us. These sensors will be included in our daily life requirements soon and they will affect our lives in both positive and negative ways. In this paper, we discuss the manner, applications and design issues for a cloud of virtual sensors, and we introduce a distributed system design to deal with physical sensors that reside in diverse locations and operate in different environments. This design operates in a cloud computing vision and can make virtual sensors in upper of physical one available from anywhere using ICT structure. Then, we negotiated the future of this technology, i.e., the Internet of Things (IoT). Additionally, we go over the strengths and weaknesses of using this technology. Our test lab shows high performance and good total cost of ownership and effective response time.